2014
DOI: 10.11634/232907811402499
|View full text |Cite
|
Sign up to set email alerts
|

Income Poverty in Nigeria: Incidence, Gap, Severity and Correlates

Abstract: This paper examined the incidence, depth and severity of poverty, and poverty correlates in Bayelsa state using the FGT decomposable class of poverty measures and a logit regression model as analytical tools on the 2009-10 NLSS data. Results from the FGT model showed that about 25 percent of households are income poor. To escape poverty the averagely poor has to mobilize financial resources to be able to meet 14 percent of N22393.62 household per capita expenditure monthly and the core poor has to mobilize fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…For instance, the result revealed that, one unit increase in the household size will increase poverty incidence by reducing poor household's per capita income by N1445.41. The result corroborates with the research findings of [1,3,8,10,13,14,17,21,22,24].…”
Section: Determinants Of Poverty Among Rural Farming Households In Aksupporting
confidence: 92%
See 1 more Smart Citation
“…For instance, the result revealed that, one unit increase in the household size will increase poverty incidence by reducing poor household's per capita income by N1445.41. The result corroborates with the research findings of [1,3,8,10,13,14,17,21,22,24].…”
Section: Determinants Of Poverty Among Rural Farming Households In Aksupporting
confidence: 92%
“…In the South-South region of Nigeria, S. Edoumiekumo, M. Tamarauntari and S. Steve [14] examined the incidence, depth and severity of poverty in Bayelsa state. Results from the logit regression showed that agriculture and household size increases the probability that a household will be poor while dwelling in the urban area; being headed by male, a naira increase in households per capita expenditure on education and per capita expenditure on health and a year's increase in the number of years spent in school by household head reduces the probability that a household will be poor.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Increase in education is often linked to increase in capital formation and adoption of risky farm exercise. The finding is in line with empirical results of Ogbonna (2012); Asogwa et al, (2012); Olawuyi and Adetunji (2013); Akinbode (2013); Adetayo (2014); Edoumiekumo et al, (2014) and Duniya and Rekwot (2015).…”
Section: Determinants Of Poverty Among Youth Farmers In Akwa Ibom Statesupporting
confidence: 91%
“…In the South-South region of Nigeria, Edoumiekumo et al, (2014) examined the incidence, depth and severity of poverty in Bayelsa state. Results from the logit regression showed that agriculture and household size increases the probability that a household will be poor while dwelling in the urban area; being headed by male, a naira increase in households per capita expenditure on education and per capita expenditure on health and a year's increase in the number of years spent in school by household head reduces the probability that a household will be poor.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This was achieved employing the monetary (income) indicator. Respondents were categorized into poor and nonpoor groups using two-third mean per-capita income as poverty line as used by Edoumiekumo et al (2014) and Igbalajobi et al (2013). Poverty line using income approach is defined as per-capita income (PCI) which is income per head per day.…”
Section: Relative Poverty Line Analysismentioning
confidence: 99%